TEACHING RECOUNT TEXT THROUGH QUANTUM TEACHING STRATEGY TO IMPROVE STUDENTS' WRITING SKILL - Pinkan ubro; Deane J Wowor; Nurmin Samola (English Education Department, 2020)
The aim of this study is to find out whether or not Quantum Teaching Strategy is effective to help students enhance their writing skills. This study was carried out at SMA Negeri 1 Manganitu. This research used quantitative research. This research is expected to be useful in providing information to teachers in teaching and learning activities so that teachers are more creative and know how to improve students' curiosity, to gain students’ interest in learning English in class. The population of this research was the students of SMA Negeri 1 Manganitu and class X that consisting of 20 students as sample. This study used a pre-experimental, pre-test, and post-test design with only one group. The researcher gathered data by asking students to complete a written test firstly also known as pre-test apply in Quantum Teaching Strategy, secondly delivered with written test also known as post-test. After these activities, the researcher analysed the data by comparing the mean score of pre-test and post-test. The result of post-test score was 78 compared to the total mean = 38.75 as the result of pre-test. This meant that Quantum Teaching Strategy was an effective way to improves students’ writing skill in recount text especially in personal recount text. It was recommended to teachers to use Quantum Teaching Strategy in order to maximize students’ capability in learning English.